Self-organization of TiO2 microparticles on the surface of a thin liquid layer due to local heating and the formation of convective cells; Journal of Molecular Liquids; Vol. 324 - Egorov R. I. Roman Igorevich; Misyura S. Ya. Sergey Yakovlevich; Morozov V. S. Vladimir Sergeevich; Zaitsev A. S. Aleksandr Sergeevich (2021, 2021)
Title screen